2000
DOI: 10.1007/s002130000486
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of clozapine, haloperidol, chlorpromazine and d-amphetamine on performance on a time-constrained progressive ratio schedule and on locomotor behaviour in the rat

Abstract: Performance on progressive ratio schedules has been proposed as a means of assessing the effects of drugs on "reinforcer efficacy". It has been proposed that the effects of neuroleptic drugs on operant behaviour are mediated by a reduction of "reinforcer efficacy". We examined the effects of two "conventional" neuroleptics (haloperidol and chlorpromazine) and an "atypical" neuroleptic (clozapine) on progressive ratio schedule performance; d-amphetamine was used as a comparison compound. In experiment 1, rats r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

38
98
4
5

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(145 citation statements)
references
References 37 publications
38
98
4
5
Order By: Relevance
“…We found that clozapine administration resulted in a horizontal leftward shift of the response functions relative to saline administration in PI trials (trials without gap). These data are consistent with an effect of clozapine on the clock stage of the internal stopwatch (MacDonald and Meck, 2005) or with an increase in reinforcer efficacy, as assessed by performance in progressive ratio schedules (Cilia et al, 2001;Mobini et al, 2000). Although the latter interpretation can not be ruled out, the fact that clozapine was shown to produce a leftward shift proportional to the timed criterion in a tri-peak procedure (MacDonald and Meck, 2005), strongly suggests that clozapine increases the speed of the internal stopwatch.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We found that clozapine administration resulted in a horizontal leftward shift of the response functions relative to saline administration in PI trials (trials without gap). These data are consistent with an effect of clozapine on the clock stage of the internal stopwatch (MacDonald and Meck, 2005) or with an increase in reinforcer efficacy, as assessed by performance in progressive ratio schedules (Cilia et al, 2001;Mobini et al, 2000). Although the latter interpretation can not be ruled out, the fact that clozapine was shown to produce a leftward shift proportional to the timed criterion in a tri-peak procedure (MacDonald and Meck, 2005), strongly suggests that clozapine increases the speed of the internal stopwatch.…”
Section: Discussionsupporting
confidence: 71%
“…Because interval timing is dependent upon DA-glutamate interactions in corticostriatal circuits Matell et al, 2003;Meck, 1996Meck, , 2005Meck, , 2006aMeck, , 2006b), these findings suggest that clozapine may affect timing and time perception directly by changes in the mechanisms of an internal stopwatch (MacDonald and Meck, 2005) or by affecting motivational systems (Cilia et al, 2001;Mobini et al, 2000). The present experiment examined the effect of i.p.…”
Section: Discussionmentioning
confidence: 95%
“…In humans with schizophrenia, amphetamine selectively improved negative symptoms (Kirrane et al 2000). Results of tests with amphetamine in previous progressive ratio studies using food reinforcement have been inconsistent: amphetamine decreased breakpoints (Schulze and Paule 1990;Caul and Brindle 2001), increased breakpoints (Poncelet et al 1983), or produced biphasic effects (Mayorga et al 2000;Mobini et al 2000). Given that procedures used in these studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…After leverresponse training was completed, one PR session (for 30 min) was conducted on the subsequent day. The PR schedule was changed every second minute according to the following exponential progression: 1, 2, 4, 6, 9, 12, 15,y, derived from the formula 5.e 0.2n 脌5, where n is the position in the sequence of ratios (Mobini et al, 2000). The so-called 'break point', the conventional index of performance on a PR schedule of reinforcement (Reilly, 1999), was defined as the first PR sequence where lever-presses decreased p50% relative to the previous sequence without increasing X100% in the following sequence.…”
Section: Behavioral Testingmentioning
confidence: 99%